Novel D-π-A organic sensitizers containing diarylmethylene-bridged triphenylamine and different spacers for solar cell application. Issue 10 (4th March 2015) - Wu, Fei; Zhao, Shangbi; Lee, Lawrence Tien Lin; Wang, Min; Chen, Tao; Zhu, Linna
Graphical abstract: Three novel D-π-A organic dyes containing diarylmethylene-bridged triphenylamine as the donor moiety, cyanoacrylic acid as the acceptor, and thiophene, benzene or furan as the π-spacers were synthesized. Dyes with furan and thiophene linkages show better planarization and electron delocalization compared to the benzene linkage. The furan unit as π-spacer provides the highest power conversion efficiency of 3.81%. Abstract: Bridged triphenylamine having almost planar core structure is a potential donor moiety for DSSCs. In this work, three novel D-π-A organic dyes TB-1, TB-2, and TB-3, containing diarylmethylene-bridged triphenylamine as the donor moiety, cyanoacrylic acid as the acceptor, and thiophene, benzene or furan as the π-spacers were synthesized and characterized for applications in dye-sensitized solar cells (DSSCs). Their photophysical, electrochemical, and photovoltaic properties were investigated, the performance of the triphenylamine donor was compared, and the effect of different π-spacers was evaluated. Results demonstrated that compared to the nonplanar triphenylamine donor, the more planar bridged TPA could offer better charge transfer process and as a result higher performances. On the other hand, in these compounds, both thiophene and furan linkages show better planarization and electron delocalization compared to the benzene linkage in this molecular system. Accordingly, dye TB-1 and TB-3 show higher IPCE and J sc values. Considering the larger V oc of dye TB-3, therefore it outperforms the other two sensitizers, exhibiting power conversion efficiency of 3.81%, with J sc of 7.54 mA cm −2 and V oc of 725 mV under simulated AM 1.5 irradiation (100 mW cm −2 ). The results are further confirmed by the EIS experiments.